NETWORK MANAGEMENT ON TOURISM POLICY DEVELOPMENT AT SINGKAWANG MUNICIPALITY - Ira Patriani (FISIP Universitas Tanjungpura, 2017)
Tourism management system is a very complex things. The production of its components is obviously handled by a variety of institutionsand coordination, both private and state and civil society. The emergence of a network approach in public policy studies because experts through various studies have found that so far, especially in developingcountries, including in Indonesia, policy activities are heavily laden with the dominance of government roles, both from planning/ formulation, implementation to policy evaluation, and provide a very minimal space for the participation of public / other public entities, such as the business world / private organizations, NGOs, interest groups, social groups(civil society)and so on. Even though it is known that this element of society is also an important element in solving the policy problem. The method used is direct observation, in-depth interviews and FGD,as well as documentation on the problem. The results obtained that the phenomenon appears in singkawang municipalityis the involvement of stakeholders outside the city of Singkawang(government)itself, including the actors or parties in question are the government supported by ODTW owners and managers, hotel owners and management, travel agents, airlines, agro-tourism community, art community, tourism event donors and others(out of state diminants). But the involvement of the parties networks has not been coordinated intensively, not on regulatedand in an ambulatory manner.